Cegah Stunting di Desa Kepuhdoko dengan (BUAS) Budidaya Asman Toga - Fahimah, Mar'atul; Suhadi, Agus; Nasirudin, Mohammad; Kirom , Ainun Zul; Rochmah, Defi Miftachur; Dzulkarnain, Muh. Zaim (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Kepuhdoko Village is a village located in Tembelang District, Jombang Regency. Data on the stunting rate in this village in 2021 is 4 children. In reducing the stunting rate, it is necessary to understand the community, especially the women of Kepuhdoko village. Prevention of stunting rates does not increase, one of which is with training activities that lead to fulfilling nutrition and increasing endurance. Training on self-care cultivation of family medicinal plants (Asmantoga) in community service was carried out. Community service activities are carried out using participatory methods for the target group, in this case, women residents of Kepuhdoko Village. Here the service executor acts as a facilitator and guide for the target group to jointly carry out the activities that have been planned. The method used is through training, demonstrating the manufacture of medicinal plant cultivation. The conclusion of community service activities, with cultivation training can increase knowledge and use of Toga for stunting prevention. Toga plants are used to increase appetite. The availability of toga plants in residents' homes can prevent stunting as early as possible and increase nutritional intake in the first 1000 days of a child's life.